THE LEARNING OF PRODUCING SHORT-STORY TEXT USING PROBLEM-BASED METHODS FOR HIGH SCHOOL STUDENTS - Aurelia Sakti Yani (Kopertis Region IV Jabar and Banten, 2020)
This research was conducted using descriptive methods. Where researchers will describe the work of students to get more detailed results. Before the research was conducted, the pretest was first held to find out more about where the students' ability was about producing short text. After that learning is done by applying the problem-based method, and ends with the posttest as a method of proving that effectiveness. The results showed that after learning to produce short text using this problem method, the ability of students to produce short stories increased. This is evidenced by the achievement of learning objectives and improved student learning outcomes. The increase can be seen from the results of the comparison of the average pretest is 56,5 and the average postest score is 69.2. Thus the posttest average is higher than the average pretest.